Defining and grading an obstructive ventilatory defect (OVD): 'FEV1/FVC lower limit of normal (LLN) vs. Z-score' and 'FEV1 percentage predicted (%pred) vs. Z-score'. Issue 1 (1st January 2018) - Kammoun, Rim; Ghannouchi, Ines; Rouatbi, Sonia; Ben Saad, Helmi
ABSTRACT: An obstructive ventilatory defect (OVD) is defined by a low forced expiratory volume/'forced/slow' vital capacity (FEV1 /FVC) (e.g. <lower limit of normal (LLN)). However, the LLN can be estimated either by the 90% confidence interval (or the 90th percentile) (American Thoracic and the European Respiratory Societies (ATS/ERS) method) or by the Z -score (global lung initiative (GLI) method). In 2014, a new alternative classification (GLI classification) for grading the OVD severity was proposed to replace the 2005-ATS/ERS one. The aims of the present study were to determine, according to the two methods (GLI vs. ATS/ERS), the frequency of participants having an OVD; and to compare the two classifications (GLI vs. ATS/ERS) of OVD severity. This was a prospective study including 1000 participants (mean age = 41 ± 10 years). The OVD was defined according to the ATS/ERS [FEV1 /FVC < LLN (=local norms value − 1.64 × residual standard deviation)] and GLI (FEV1 /FVC Z -score < −1.64) criteria. The following OVD classifications severity were applied: ATS/ERS (FEV1 %pred): mild (>70%), moderate (60–69%), moderately severe (50–59%), severe (35–49%), and very severe (<35%) and GLI (FEV1 Z -score): mild (≥ −2.0), moderate (−2.0 to −2.5), moderately severe (−2.5 to −3.0), severe (−3.0 to −4.0), and very severe (<−4.0). The frequencies of OVD were 14.4% (ATS/ERS method) and 10.5% (GLI method) ( p  < 0.05). Among the 103 participants having an OVD according to the two methods, the severity classification was mild (34.95% vs. 37.86%, p  < 0.05), moderate (25.24% vs. 18.45%, p  < 0.05), moderately severe (23.30% vs. 15.53%, p  = 0.144), severe (9.71% vs. 20.39%, p  < 0.05), and very severe (6.80% vs. 7.77%, p  = 0.785), respectively for the ATS/ERS and GLI classifications. The two OVD definitions were not exchangeable. Moreover, the two grading severity systems misclassified the OVD grades.